2013
DOI: 10.1002/ange.201208206
|View full text |Cite
|
Sign up to set email alerts
|

Ein Molekül, zwei Atome, drei Ansichten, vier Bindungen?

Abstract: Was kçnnte einfacher sein als C 2 , ein wohlbekanntes zweiatomiges Molekül mit der zweitstärksten homonuklearen Bindung (bezüglich Atomisierung)? Nun, es stellt sich heraus, dass dieses Molekül -wie der vorliegende Trialog zeigt -in einem Mikrokosmos viele Fragen zur chemischen Bindung vereint, die (auf kreative Art) Chemiker beschäftigen. Alles begann, als einer der Autoren zwei lebhafte Artikel zur Bindung in C 2 publizierte. Ein zweiter Autor wurde einbezogen, als er in einem Blog (etwas Neumodisches in der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 69 publications
0
26
0
1
Order By: Relevance
“…For L = PPh 3 , these were reported nearly 50 years ago, but not crystallograpically characterised (23).…”
Section: Recent Synthetic Accomplishmentsmentioning
confidence: 91%
See 1 more Smart Citation
“…For L = PPh 3 , these were reported nearly 50 years ago, but not crystallograpically characterised (23).…”
Section: Recent Synthetic Accomplishmentsmentioning
confidence: 91%
“…Dicarbon itself is a fascinating molecule that continues to challenge chemists with respect to the description of its bonding. [23] Recent studies even suggest the possibility of a C À C quadruple bond; [24] however, a vigorous discussion on the matter is on-going. [25] We have performed a theoretical study on bis-NHC (12)-and bis-phosphine (13)-stabilised C 2 .…”
Section: Group 14mentioning
confidence: 99%
“…An understanding of weak mutual interactions between atoms or functional groups as structure-governing entities therefore lies at the heart of chemistry.I nareview article published in 2015, [1] Schreiner and Wagner highlighted the importance of London dispersion forces,t he attractive term of van der Waals interactions,i nm any areas of chemistry.T he increasing importance of recognizing and describing such interactions properly has called theoreticians to design elaborate methods for including the treatment of London dispersion forces into powerful computational procedures.E rrors in DFT calculations generally accumulate with molecular size, [2] often because of insufficient consideration of London dispersion (LD) interactions,w hich are largely ignored in many established DFT methods. Their solid-state structures are dominated by intermolecular p stackingi nteractions,p rimarily leading to dimeric or chaintype aggregates.Analysis of free molecules in the gas phase by electron diffraction revealed the most abundant conformer to be significantly stabilized by intramolecular p-p interactions.…”
mentioning
confidence: 99%
“…An understanding of weak mutual interactions between atoms or functional groups as structure-governing entities therefore lies at the heart of chemistry.I nareview article published in 2015, [1] Schreiner and Wagner highlighted the importance of London dispersion forces,t he attractive term of van der Waals interactions,i nm any areas of chemistry.T he increasing importance of recognizing and describing such interactions properly has called theoreticians to design elaborate methods for including the treatment of London dispersion forces into powerful computational procedures.E rrors in DFT calculations generally accumulate with molecular size, [2] often because of insufficient consideration of London dispersion (LD) interactions,w hich are largely ignored in many established DFT methods. An understanding of weak mutual interactions between atoms or functional groups as structure-governing entities therefore lies at the heart of chemistry.I nareview article published in 2015, [1] Schreiner and Wagner highlighted the importance of London dispersion forces,t he attractive term of van der Waals interactions,i nm any areas of chemistry.T he increasing importance of recognizing and describing such interactions properly has called theoreticians to design elaborate methods for including the treatment of London dispersion forces into powerful computational procedures.E rrors in DFT calculations generally accumulate with molecular size, [2] often because of insufficient consideration of London dispersion (LD) interactions,w hich are largely ignored in many established DFT methods.…”
mentioning
confidence: 99%
“…
C 2 · chemical bonding · multiconfigurational systems · quadruple bond Sason: Frenking and Hermann have criticized our work in Nature Chemistry and the trialogue in Angewandte Chemie on quadruple bonding in C 2 , [1,2] and raised some useful points, which I thought I may be able to answer with some hard facts.In the trialogue, [2] I argued that one can put an experimental value on the bond energy of the 4th bond in C 2 , using the difference between the successive bond dissociation energies (BDEs) of the two C À H bonds of acetylene. Using the experimental and theoretical data, Henry and I showed that BDE(CH-1) = 133.5 kcal mol À1 and BDE(CH-2) = 116.7 kcal mol À1 , which leads to BDE(4th) = 16.8 kcal mol À1 as the experimental bond energy of the 4th bond.
…”
mentioning
confidence: 99%